Devotional response that arises in the agreement between the captain gold driver with the TPI grab's participants - Hishom Prastyo Akbar (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
The emergence of the phenomenon of Taxi Online / Motorized Vehicles Not in Route Like the welcome for consumers of financial institutions, especially the ease of procession of registering vehicles for online taxis certainly adds to the passion of the community to run this business, unfortunately not only the benefits that may be obtained by financial institutions business activists consumers but also risks, Bisnis Taxi Online as the application seller does not require registration of vehicle status in detail, regarding whether the vehicle registered is an object of fiduciary guarantee or not. Responding to the need for a vehicle with a secure credit system, Grab as one of the giant companies in online transportation mode, has raised / collaborated with companies known as Indonesian Transportation Technology / TPI Preferred Grab's Partner, as a driver / driver business partner by offering ease of ownership vehicles for taxi purposes online through the Gold Captain program.